Optimizing Nitrogen Fixation and Recycling for Food Production in Regenerative Life Support Systems - Langenfeld, Noah J.; Kusuma, Paul; Wallentine, Tyler; Criddle, Craig S.; Seefeldt, Lance C.; Bugbee, Bruce (Frontiers in Astronomy and Space Sciences, 2021)
Nitrogen (N) recycling is essential for efficient food production in regenerative life support systems. Crew members with a high workload need 90 to 100 grams of protein per person per day, which is about 14 grams of N, or one mole of N, per person per day. Most of this N is excreted through urine with 85% as urea. Plants take up N predominantly as nitrate and ammonium, but direct uptake as urea is possible in small amounts. Efficient N recycling requires maintenance of pH of waste streams below about 7 to minimize the volatilization of N to ammonia. In aerobic reactors, continuous aerobic conditions are needed to minimize production and volatilization of nitrous oxide. N is not well recycled on Earth. The energy intensive Haber-Bosh process supplies most of the N for crop production in terrestrial agriculture. Bacterial fixation of dinitrogen to ammonium is also energy intensive. Recycling of N from plant and human waste streams is necessary to minimize the need for N fixation. Here we review approaches and potential for N fixation and recycling in regenerative life support systems. Initial estimates indicate that nearly all the N from human and plant waste streams can be recovered in forms usable for plants.